PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MODEL PEMBELAJARAN ICARE (INTRODUCTION, CONNECT, APPLY, REFLECT, AND EXTEND) PADA MATERI MOMENTUM DAN IMPULS KELAS X SMA - Mulida Samisiani; Zulhelmi Zulhelmi; Muhammad Sahal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract:The learning device developed is a physics learning device using the Argument ICARE (Introduction, Connect, Apply, Reflect, Extend) model to improve cognitive learning outcomes of class X SMA student on momentum and impulse, consisting of a learning outcomes test instrument. The purpose of this study was to produce a physics learning device using a valid Argument ICARE (Introduction, Connect, Apply, Reflect, Extend) model and was used to improve cognitive learning outcomes of class X SMA students on momentum adn impulse. This reseach is expected to be a reference for making innovative learning tools and can be used as a foundation in the teaching and learning objectives can be achieved. This type of research is a Research and Development (R&D) using the 4D model. This research is only limited to the development stage. The research instrument used was the RPP validation assessment sheet, LKPD, and the cognitive learning outcome test instrument used by the validator to assess learning tools. Data analysis in this study used descriptive analysis, by calculating the validity score of each indicator of the learning device. The results showed that the physics learning device using the ICARE (Introduction, Connect, Apply, Reflect, Extend) model was declared valid with the overall score of the device being 3.15 with a high category, so it was declarated feasible to be used for teaching in class X SMA in an effort to improve student cognitive learning outcomes on momentum and impulse.Key Words: Physics Learning Tools, ICARE Model, Cognitive Learning Outcomes, Momentum and Impulse.